The Supershear Earthquake (M 7.7) in Mandalay, Myanmar on 28th March 2025 - , Hla Hla Aung (Archives of Current Research International, 2025)
On March 28, 2025, at 12:50:52 PM local time in Myanmar, a powerful earthquake with a moment magnitude (Mw) of 7.7 struck near Mandalay in Upper Myanmar. The quake lasted approximately 85 seconds, with an epicenter at latitude 21.996ºN and longitude 95.926ºE, at a shallow depth of 10km. A second earthquake of magnitude 6.4 followed just 12 seconds later. Both events occurred along the Sagaing Fault within its fault zone. These quakes caused widespread destruction across central Myanmar and were followed by numerous aftershocks, including a Mw 5.1 quake on March 30, 2025. A detailed study of these events is essential to understand their seismic mechanisms. Fault characteristics were investigated using satellite imagery, seismic data, fault plane solutions, and active tectonic assessments. Findings show that the epicenter is located near the Yega Inn tectonic lake, a pull-apart basin formed by extensional faulting and minor strike-slip motion. Resonance amplification in lake-bed sediments contributed to the earthquake's intensity.